1987
DOI: 10.1007/bf02596305
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among medical and surgical patients nearing hospital discharge

Abstract: Ninety-eight medical and surgical inpatients were interviewed 24-72 hours prior to discharge. Thirty-five (36%) had clinical levels of anxiety and depression as defined by the SCL-90-R, a self-report symptom inventory. Compared with patients with normal SCL-90-R subtest scores, anxious and depressed patients more often had the following characteristics: older age, black race, lower socioeconomic class, a recent previous hospitalization, and impaired functional status prior to admission. Three to four weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Other self‐rating depression scales utilized in examining the prevalence of depressive symptoms in the medically ill include the General Health Questionnaire, 54 SCL‐90, 55,56 Beck Depression Inventory, 42,54 Zung Self‐Rated Depression Scale, 53,55 and General Health Questionnaire 54 . None of these scales except for the Zung Scale, 53 however, has been validated for their usefulness in detecting major depression in older medically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other self‐rating depression scales utilized in examining the prevalence of depressive symptoms in the medically ill include the General Health Questionnaire, 54 SCL‐90, 55,56 Beck Depression Inventory, 42,54 Zung Self‐Rated Depression Scale, 53,55 and General Health Questionnaire 54 . None of these scales except for the Zung Scale, 53 however, has been validated for their usefulness in detecting major depression in older medically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined age and racial differences in reports of self-rated depressive symptoms in medical inpatients, and results have been conflictive. Investigators variably report higher rates in younger patients [6], in older patients [lo], in blacks [6,10]; a number have found little relationship with either age or race [4,11,261. One study reported an interaction between age, sex, and race, with the highest rates reported for young black males [6].…”
Section: Physical Health Variablesmentioning
confidence: 99%
“…In previous studies, only severity of the medical illness has been consistently linked to self-rated depressive symptoms [2,4,[9][10][11]261. Other more variably reported correlates have included medical diagnosis (neurological) [8], low socioeconomic status or social class [2, 9, lo], low social support [ll], low educational level [ll], male sex [2], female sex [8], and religious denomination (Jewish) [4].…”
Section: Physical Health Variablesmentioning
confidence: 99%
“…The outcome after hospital discharge of medical patients with major depressive disorder, regardless of age, has not yet been studied. Walker et al (1987) report that 48% (12/25) of patients scoring above the usual cutoff on the Symptom Distress Checklist during their hospital stay had scores within the normal range on followup three to four weeks after hospital discharge. Scoring above the normal range on a symptom checklist, however, is not the same as major depressive disorder.…”
mentioning
confidence: 99%